RECOGNITION OF PRODUCTS THROUGH THE WEB APPLICATION (WEB SITE) IN STORES ADVENTURER WORKSHOP "BOLDER" USING MACROMEDIA DREAMWEAVER MX 6.0 - Mugi Prasetyo; Diyah Ruri Irawati,Skom,MMSI Diyah Ruri Irawati,Skom,MMSI (Jurnal Sistem Informasi, 2005)
Increase the control and accelerate product introduction process can be quickly andaccurately so that helps in the process of developing the product marketing activities.In using computerized porgram, then the data needed, whether products or customerswill be efficient and can be defined, this resulted in any change of data needed to beresolved properly.the provision of information will be faster and more efficientÃ˜Process.